A Global Perspective on Export Diversification: Determinants and Regional Insights from 93 Countries - Zheng, H.; Someya, M.; Okamuro, M. (Colombo Economic Journal, 2024)
A central structural challenge for developing economies is the diversification of their export structures. Reliance on a narrow range of commodities renders these economies susceptible to the volatility of commodity prices. This paper addresses a fundamental question: What are the key determinants of export diversification? We investigate the question using the Herfindahl-Hirschman Index (HHI) as a measure of export structure diversification, analyzing panel data from 2010 to 2019 across 93 countries. Our findings reveal that domestic credit to GDP aids in diversifying exports, whereas the presence of commercial bank branches tends to increase the concentration of exports. Exporting to high-income countries tends to decrease export diversification, while importing from such countries aids in diversifying the export structure. The spatial-lagged HHI, which accounts for the export structures of geographically proximate nations, shows significant influence in East Asia. Additionally, to support export diversification, the required level of education varies across different regions.
Keywords: Export Diversification; Herfindahl-Hirschman Index; Spatial Lag; Natural Resource Rent; Access to Finance; Regional Difference